Empirically defining treatment response and remission in body dysmorphic disorder. Issue 1 (30th January 2021) - Fernández de la Cruz, Lorena; Enander, Jesper; Rück, Christian; Wilhelm, Sabine; Phillips, Katharine A.; Steketee, Gail; Sarvode Mothi, Suraj; Krebs, Georgina; Bowyer, Laura; Monzani, Benedetta; Veale, David; Mataix-Cols, David
Abstract: Background: The number of clinical trials in body dysmorphic disorder (BDD) has steadily increased in recent years. As the number of studies grows, it is important to define the most empirically useful definitions for response and remission in order to enhance field-wide consistency and comparisons of treatment outcomes across studies. In this study, we aim to operationally define treatment response and remission in BDD. Method: We pooled data from three randomized controlled trials of cognitive-behavior therapy (CBT) for BDD (combined n = 153) conducted at four academic sites in Sweden, the USA, and England. Using signal detection methods, we examined the Yale-Brown Obsessive Compulsive Scale modified for BDD (BDD–YBOCS) score that most reliably identified patients who responded to CBT and those who achieved remission from BDD symptoms at the end of treatment. Results: A BDD–YBOCS reduction ⩾30% was most predictive of treatment response as defined by the Clinical Global Impression (CGI) – Improvement scale (sensitivity 0.89, specificity 0.91, 91% correctly classified). At post-treatment, a BDD–YBOCS score ⩽16 was the best predictor of full or partial symptom remission (sensitivity 0.85, specificity 0.99, 97% correctly classified), defined by the CGI – Severity scale. Conclusion: Based on these results, we propose conceptual and operational definitions of response and full or partial remission in BDD. A consensus regarding these constructs will improve the interpretation and comparison of future clinical trials, as well as improve communication among researchers, clinicians, and patients. Further research is needed, especially regarding definitions of full remission, recovery, and relapse.